Nanoscale borosilicate bioactive glass for regenerative therapy of full-thickness skin defects in rabbit animal model - Elshazly, Noha; Saad, Manal M.; El Backly, Rania M.; Hamdy, Ayat; Patruno, Marco; Nouh, Samir; Saha, Suman; Chakraborty, Jui; Marei, Mona K. (Frontiers in Bioengineering and Biotechnology, 2023)
Bioactive glass (BG) occupies a significant position in the field of hard and soft tissue regeneration. Different processing techniques and formulas have been introduced to expand their regenerative, angiogenic, and antibacterial properties. In the present study, a new formula of borate-based bioactive glass nanofibers was prepared and tested for its wound healing efficacy in a healthy and diabetic rabbit model. The glass formula ((1-2) mol% of B2O3,(68-69)mol% of SiO2, and (29-30)mol% of CaO) was prepared primarily by the sol-gel technique followed by the electrospinning technique. The material was characterized for its ultrastructure using scanning electron microscopy, chemical composition using FTIR, and its dynamic in vitro biodegradability using ICP-AES. Twelve healthy rabbits and one diabetic rabbit were subjected to surgical induction of full-thickness skin defects using a 1 cm2 custom-made skin punch. The bioactive glass nanofibers were used as a grafting material in 7 experimental rabbits, while the defects in the remaining rabbits were considered as the negative control samples. All defects were assessed clinically for the decrease in wound size and clinical signs of healing and histologically for angiogenesis, inflammatory response, cell recruitment, epithelial lining, and formation of skin appendages at 1,2 and 3 weeks following the intervention. Structural analysis of the glass fibers confirmed their nano-size which ranged from 300nm to 700nm. Moreover, the chemical analysis confirmed the presence of SiO2 and B2O3 groups within the structure of the nanofibers. Additionally, dynamic biodegradation analysis confirmed the rapid degradation of the material starting from the first 24h and rapid leaching of calcium, silicon, and boron ions confirming its bioactivity. The wound healing study of the nanofibrous scaffold confirmed its ability to accelerate wound healing and the closure rate in both healthy and diabetic rabbits. Histological analysis of the defects confirmed the angiogenic, regenerative and antibacterial ability of the material throughout the study period in healthy and diabetic animals. The results unveil the powerful therapeutic properties of the formed nanofibers and open a new gate for more experimental and clinical applications.